Reflecting on the Themes of Aging, Caregiving, Narrative, and Multiculturalism in the EFCT Case of "Alice" and "Steve"' - Mendelson, Drew (Pragmatic Case Studies in Psychotherapy, 2024)
In this article, I respond to commentaries by Drs. Karen Skean and Elisabeth Brown (2024), and by Dr. Shalonda Kelly (2024) on my presentation of the case of "Alice" and "Steve" (Mendelson, 2024), a later-life couple I treated using Emotionally Focused Couple Therapy (EFCT). Skean and Brown (2024) meaningfully address the role of EFCT in redefining a relationship narrative within the contexts of caregiving, illness, and loss, drawing from Erik Erikson’s final psychosocial stage of integrity vs. despair and highlighting the benefits of teletherapy for broader access. Kelly (2024) thoughtfully acknowledges both the possibilities and limitations of integrating EFCT and multiculturalism in treating diverse couples, noting areas where the therapist can bridge differences in partners’ worldviews; power; experiences and contexts; and felt sense of distance. In the following response, I reflect on their emotionally and intellectually compelling commentaries and offer feedback to foster discussion on the adaptation of EFCT to work within our clients’ unique generational and cultural frameworks.